Readiness of the SME Sector for Market Changes Arising from The Fourth Industrial Revolution - Oliwia SLUSARCZYK (Communications of International Proceedings, 2022)
The future of SMEs, which are the main participants of most industries and countries, significantly depends on the ability to respond to customer expectations while maintaining a competitive advantage in their market. Industry 4.0 technologies may allow companies to iprove their cost efficiency and product differentiation, thus allowing SMEs to use new market opportunities and increase financial profits. Preparation for Industry 4.0 requires the change in the approach of enterprises to their management and some irreversible changes. At the same time, the change management process is long-term, in turn, the dynamics of Industry 4.0 solutions is very fast. Therefore, the objective of the article is to assess the preparation and implementation of changes in SMEs enforced by Industry 4.0. It was assumed that change management is determined by the company’s size, its market operation time, and the scope of activities.
Keywords: SME; market changes; readiness for changes; Fourth Industrial Revolution